2014
DOI: 10.1007/s00374-014-0958-z
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of cover crops on ‘hot spot’ arbuscular mycorrhizal fungal communities in organic tomato

Abstract: Arbuscular mycorrhizal fungal (AMF) communities are fundamental in organic cropping systems where they provide essential agro-ecosystem services, improving soil fertility and sustaining crop production. They are affected by agronomic practices, but still, scanty information is available about the role of specific crops, crop rotations and the use of winter cover crops on the AMF community compositions at the field sites. A field experiment was conducted to elucidate the role of diversified cover crops and AMF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 59 publications
5
45
2
4
Order By: Relevance
“…A higher species richness than in our study was detected in Mediterranean semi-arid environments (Torrecillas et al 2012). Using a morphological approach, a previous study on the occurrence of AMF spores in an organic field located in the same area detected a very high number of AMF species (58), never reported from a single site (Njeru et al 2015). The lower number of species detected in the present work, compared with such a study, may be a consequence of the specific environment of the Bhot spot area^, the methodology used (morphological vs molecular) or the material analysed (spores vs roots).…”
Section: Identification Of Root Colonizing Amfcontrasting
confidence: 70%
See 2 more Smart Citations
“…A higher species richness than in our study was detected in Mediterranean semi-arid environments (Torrecillas et al 2012). Using a morphological approach, a previous study on the occurrence of AMF spores in an organic field located in the same area detected a very high number of AMF species (58), never reported from a single site (Njeru et al 2015). The lower number of species detected in the present work, compared with such a study, may be a consequence of the specific environment of the Bhot spot area^, the methodology used (morphological vs molecular) or the material analysed (spores vs roots).…”
Section: Identification Of Root Colonizing Amfcontrasting
confidence: 70%
“…Phylotypes affiliated to Archaeospora trappei, D. epigaea and Paraglomus sp. were also detected, although rarely and associated to single plant species, confirming their occurrence in the area (Njeru et al 2015).…”
Section: Identification Of Root Colonizing Amfsupporting
confidence: 56%
See 1 more Smart Citation
“…We could have overlooked AMF species that produce spores rarely or seasonally (Njeru et al 2015). Moreover, by sampling to the depth of 20 cm, some part of spore diversity that exclusively occurred in the subsoils might have been missed (Oehl et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a low AMF species richness (only 5) was found in the rhizospheric soils associated to pioneer plant species growing at the mouth of lake Budi, Chile (Medina et al, 2015); nevertheless, one of these corresponds to a new specie Corymbiglomus pacificum (Medina et al, 2014). On the contrary, enormous species richness was found in organic tomato in a Mediterranean site with 58 AMF species belonging to 14 genera (Njeru et al, 2015). Maurer et al (2014) reported 38 AMF species under no-till and in temperate grasslands Oehl et al (2010) found between 34-39 AMF species and Saito et al (2004) in Japan reported least amount with 24 taxa at two sites.…”
Section: Indicators Used To Evaluate Amf Diversitymentioning
confidence: 93%